Indonesia's electricity demand and the coal sector: export or meet domestic demand? - Cornot-Gandolphe, S (Oxford Institute for Energy Studies, 2017)
Driven by rapidly increasing electricity demand, Southeast Asia coal demand has surged since 2010. The availability of coal in the region, and its lower cost than competing fuels, has made coal the preferred option to fuel rising power demand. The region added 25 GW of coal-based capacity in the past five years, accounting for 42 per cent of total additional generation capacity. Even the gas-producing countries in the region have introduced more coal in their electricity mix as gas shortages pushed them to diversify their mix. However, this shift compromises the national commitments taken by Southeast Asian governments to reduce their greenhouse gas emissions. In the wake of the Paris Agreement, national governments across the region have started to reassess their power development plans, introducing more renewable energy sources, promoting energy efficiency measures, and reducing the contribution of coal in the electricity mix. This reassessment, however, does not constitute a shift away from coal. Despite the scale back, coal still dominates the targeted additional capacity, followed by natural gas, hydropower, and other renewables: there are 29 GW of coal-based capacity under construction in the region, most of them to be completed by 2020. In addition, there is a huge number of permitted and announced coal-fired power plants in the pipeline, which means that the shift towards coal may continue well after 2020. The growth in Southeast Asian coal demand is therefore mixed: until 2020, it is expected to be steep as more coal-fired power plants are commissioned, but after that date, the rate of growth is expected to slow down significantly. The wide range of outlooks for future coal demand has a significant impact on regional coal trade.